Defining Breast Cancer Intrinsic Subtypes by Quantitative Receptor Expression. (23rd April 2015) - Cheang, Maggie C.U.; Martin, Miguel; Nielsen, Torsten O.; Prat, Aleix; Voduc, David; Rodriguez-Lescure, Alvaro; Ruiz, Amparo; Chia, Stephen; Shepherd, Lois; Ruiz-Borrego, Manuel; Calvo, Lourdes; Alba, Emilio; et al.
Abstract: Purpose: To determine intrinsic breast cancer subtypes represented within categories defined by quantitative hormone receptor (HR) and HER2 expression. Methods: We merged 1, 557 cases from three randomized phase III trials into a single data set. These breast tumors were centrally reviewed in each trial for quantitative ER, PR, and HER2 expression by immunohistochemistry (IHC) stain and by reverse transcription-quantitative polymerase chain reaction (RT-qPCR), with intrinsic subtyping by research-based PAM50 RT-qPCR assay. Results: Among 283 HER2-negative tumors with <1% HR expression by IHC, 207 (73%) were basal-like; other subtypes, particularly HER2-enriched (48, 17%), were present. Among the 1, 298 HER2-negative tumors, borderline HR (1%–9% staining) was uncommon ( n = 39), and these tumors were heterogeneous: 17 (44%) luminal A/B, 12 (31%) HER2-enriched, and only 7 (18%) basal-like. Including them in the definition of triple-negative breast cancer significantly diminished enrichment for basal-like cancer ( p < .05). Among 106 HER2-positive tumors with <1% HR expression by IHC, the HER2-enriched subtype was the most frequent (87, 82%), whereas among 127 HER2-positive tumors with strong HR (>10%) expression, only 69 (54%) were HER2-enriched and 55 (43%) were luminal (39 luminal B, 16 luminal A). Quantitative HR expression by RT-qPCR gave similar results. Regardless of methodology, basal-like cases seldom expressed ER/ ESR1 or PR/ PGR and were associated with the lowest expression level of HER2/ ERBB2 relative to other subtypes. Conclusion: Significant discordance remains between clinical assay-defined subsets and intrinsic subtype. For identifying basal-like breast cancer, the optimal HR IHC cut point was <1%, matching the American Society of Clinical Oncology and College of American Pathologists guidelines. Tumors with borderline HR staining are molecularly diverse and may require additional assays to clarify underlying biology. Abstract : This study compared centrally performed clinical assays of quantitative ER, PR, and HER2 expression with molecular intrinsic subtypes identified by an open-source, centroid-based, subtype predictor in tumors collected across three phase III randomized clinical trials and determined the molecular populations within strongly hormone receptor-positive tumors, borderline tumors, and triple-negative tumors.